2019
DOI: 10.1073/pnas.1903838116
|View full text |Cite
|
Sign up to set email alerts
|

Adult sex ratio influences mate choice in Darwin’s finches

Abstract: The adult sex ratio (ASR) is an important property of populations. Comparative phylogenetic analyses have shown that unequal sex ratios are associated with the frequency of changing mates, extrapair mating (EPM), mating system and parental care, sex-specific survival, and population dynamics. Comparative demographic analyses are needed to validate the inferences, and to identify the causes and consequences of sex ratio inequalities in changing environments. We tested expected consequences of biased sex ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 92 publications
4
39
0
Order By: Relevance
“…The lineage was initiated by hybridization of an immigrant Geospiza conirostris with a resident G. fortis, resulting in the formation of a reproductively isolated population that displayed allometric transgression, that is, a deviation from the two species in the relationship between beak size and body size (27,78). Transgressive morphology is implicated in reproductive isolation because mate choice is based in part on beak and body size (61,62,72) and the relationship between the two (79).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lineage was initiated by hybridization of an immigrant Geospiza conirostris with a resident G. fortis, resulting in the formation of a reproductively isolated population that displayed allometric transgression, that is, a deviation from the two species in the relationship between beak size and body size (27,78). Transgressive morphology is implicated in reproductive isolation because mate choice is based in part on beak and body size (61,62,72) and the relationship between the two (79).…”
Section: Discussionmentioning
confidence: 99%
“…Known hybrids were observed to breed from 1983 onward when an El Niño event caused a major change to the environment (56,60). Hybrids were found to backcross according to the same rules that govern intraspecific mate choice: finches choose mates on the basis of imprinting on paternal song and parental morphology, and occasionally hybridize when they learn the song of another species (61,62). Frequencies of alleles at 16 unlinked polymorphic loci are used here to assign 3,165 individuals probabilistically (≥0.9) to the three species (63), and, if the 0.9 criterion is not met, they are assigned to hybrids (admixtures).…”
Section: Significancementioning
confidence: 99%
“…This finding was found in the blue tit (García-Navas et al, 2013;Schlicht & Kempenaers, 2013), the dark-eyed junco , Junco hyemalis (Gerlach, McGlothlin, Parker, & Ketterson, 2012), the hihi, Notiomystis cincta (Walker, Ewen, Brekke, & Kilner, 2014)), the mountain bluebird, Sialia currucoides (Balenger, Scott Johnson, Mays Jr, & Masters, 2009), and the white-crowned sparrow, Zonotrichia leucophrys (Poesel, Gibbs, & Nelson, 2011). Interestingly in addition, in two species of Darwin finches (Geospiza fortis & G. scandens) for which mating patterns change when environmental fluctuations alter sex ratios, females of both species were more frequently polyandrous in male-biased populations, and fledged more offspring by changing mates (Grant & Grant, 2019). Lastly, in cooperative breeding species, a positive Bateman gradient was found in females but not in males for the superb starling, Lamprotornis superbus (Apakupakul & Rubenstein, 2015).…”
Section: Progress In Understanding the Strength Of Sexual Selection Omentioning
confidence: 99%
“…Shorter-term experiments would also be of interest. For example, ecological factors such as density (Aronsen, Berglund, Mobley, Ratikainen, & Rosenqvist, 2013), food availability (Janicke, David, & Chapuis, 2015) or sex ratio (Grant & Grant, 2019) could be modified to test how environmental conditions affect the opportunity for sexual and social selection in females.…”
Section: Progress In Understanding the Strength Of Natural Selection mentioning
confidence: 99%
“…Re-mating opportunities determine who gains more from deserting the family and who gains more from care (Balshine-Earn & Earn, 1998;Eldegard & Sonerud, 2009;Fujioka, 1989;Keenleyside, 1985;Pilastro, Biddau, Marin, & Mingozzi, 2001;Roulin, 2002;Thomson et al, 2014). Recent studies have shown that reproductive behaviour is often tied to sex ratios of the adult population (Grant & Grant, 2019;Kokko & Jennions, 2008;Liker, Freckleton, & Székely, 2013) with biased sex ratios altering potential for sequential polygamy in each sex. In that case, the rarer sex has a higher opportunity for polygamy and is more likely to desert the brood (Eberhart-Phillips et al, 2018).…”
Section: Introductionmentioning
confidence: 99%